2023
DOI: 10.3389/fmicb.2023.1232358
|View full text |Cite
|
Sign up to set email alerts
|

Host habitat rather than evolutionary history explains gut microbiome diversity in sympatric stickleback species

Aruna M. Shankregowda,
Prabhugouda Siriyappagouder,
Marijn Kuizenga
et al.

Abstract: Host-associated microbiota can influence host phenotypic variation, fitness and potential to adapt to local environmental conditions. In turn, both host evolutionary history and the abiotic and biotic environment can influence the diversity and composition of microbiota. Yet, to what extent environmental and host-specific factors drive microbial diversity remains largely unknown, limiting our understanding of host-microbiome interactions in natural populations. Here, we compared the intestinal microbiota betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 74 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…Initial studies have begun to explore the influence of host ecology, genotype, diet, geographic distance and habitat type on gut microbial diversity. A study across co-occurring threespine stickleback and ninespine stickleback ( Pungitius pungitius ), two species that diverged around 26 million years ago [ 23 ], found that a larger proportion of gut microbiota variation was explained by habitat type than by host species identity [ 24 ]. Variation in the gut microbiota of a wild stickleback population has been shown to be influenced by diet diversity, sex and the immune system of the host [ 16 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies have begun to explore the influence of host ecology, genotype, diet, geographic distance and habitat type on gut microbial diversity. A study across co-occurring threespine stickleback and ninespine stickleback ( Pungitius pungitius ), two species that diverged around 26 million years ago [ 23 ], found that a larger proportion of gut microbiota variation was explained by habitat type than by host species identity [ 24 ]. Variation in the gut microbiota of a wild stickleback population has been shown to be influenced by diet diversity, sex and the immune system of the host [ 16 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%